2022
DOI: 10.4103/jwas.jwas_101_22
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Prevalence, Severity, and Pattern Among Male Adolescents in Kano, Nigeria

Abstract: Background: Dental caries is the most common oral disease of mankind; however, there are limited data on the oral status of adolescents in northern Nigeria. Recently, the World Health Organization set the global caries goal as significant caries (SiC) index score of <3. This study was designed to appraise the magnitude of the disease among adolescents in northern Nigeria. Objectives: The objective of the study was to determine the prevalence, pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Higher prevalence was also reported by Andegiorgish et al (26) in Eritrea (78.0%) and Akaji et al (27) in Nigeria (54.4 %) . Another recent Nigerian study in 2022 reported 71.8% and 28.8% in mandibular and maxillary first molars, respectively in 12-year-olds (28). However, the prevalence in Romania ( 7) was reported as 25.82%, and in the Zhejiang Province in China the prevalence in urban areas was 24.3%, whilst in rural areas 26.9% (29).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Higher prevalence was also reported by Andegiorgish et al (26) in Eritrea (78.0%) and Akaji et al (27) in Nigeria (54.4 %) . Another recent Nigerian study in 2022 reported 71.8% and 28.8% in mandibular and maxillary first molars, respectively in 12-year-olds (28). However, the prevalence in Romania ( 7) was reported as 25.82%, and in the Zhejiang Province in China the prevalence in urban areas was 24.3%, whilst in rural areas 26.9% (29).…”
Section: Discussionmentioning
confidence: 95%
“…The use of fluoride varnish as a caries prevention measure will produce prevention results similar to those achieved by using fissures sealants in first permanent molars (33). A recent study by Chizoba et al recommended interventions such as the sealing of the pits and fissures of molar teeth from the age of 6 years, as well as other evidence-based strategies (28).…”
Section: Discussionmentioning
confidence: 99%